Kelangsungan dan Perubahan Rumah Adat Batak Toba pada Masa Kini - Natania Nurafni; Arif Laksono; Fany Chairina; Wiranto Sillahi; Yeyen Zepania Br. Tobing; Syareefa Reihan Maryam; Ilham Amri (Journal of Creative Student Research, 2024)
House The traditional house of the Toba Batak, known as "Rumah Bolon", is a symbol of the culture and identity of the Toba Batak community. culture and identity of the Toba Batak community. This research aims to examine the continuity and changes that have occurred in the Toba Batak traditional houses in the the present. The research method used is to explore information from several previous studies as references. as a reference, besides that researchers also dig information from books in order to get an existing information. in order to get information that has existed before. The results The results show that although there are still some traditional houses that are maintained and preserved, most of the traditional houses have experienced maintained and preserved, most of the traditional houses have undergone significant changes. significant changes. These changes include aspects of architecture, function, and building materials used. Factors such as modernization, economic economic needs, and external cultural influences have contributed to these changes. Research This research concludes that although Toba Batak traditional houses have undergone various changes, preservation efforts are still needed to maintain cultural values. changes, preservation efforts are still needed to maintain the cultural and historical values contained in it. and history contained in it. Implementation of preservation policies preservation policies and increasing public awareness about the importance of traditional houses as cultural heritage are the main recommendations in this research.